Biomolecular catalysis - Jungbae Kim; editor; Seong H. Kim; editor; Ping Wang; editor (Distributed by Oxford University Press, 2008)
The first part of the book describes the use of various nanostructures, including nanoporous materials, nanotubes, nanofibers and nanoparticles, and composite materials for biocatalysis. These chapters demonstrate the current frontier exploration and the most popular structures for nanobiocatalysis. The second part of the book illustrates potential applications of nanoscale biocatalysts in heterogeneous catalysis, biosensors, energy conversion, reaction engineering, and nano-transport